Elimination Of Manganese Interference With EDTA Masking In Determination of Nickel and Lead In Pyrolusite Using Atomic Absorption Spectrophotometry - Anggelinus Nadut; Landi Pote, Lodowik (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2023)
ABSTRACT Research has been carried out on the elimination of manganese interference with EDTA masking in the determination of nickel and lead in pyrolusite using Atomic Absorption Spectrophotometry (AAS) with an air-acetylene flame. Dissolution of pyrolusite samples was carried out by wet digestion using aqueous regia and HF solutions with a ratio of 3:4 (v/v). Interference studies were carried out on the absorbance of nickel and lead with the addition of manganese with varying concentrations of 100-5000 μg/mL measured at a wavelength of 232.0 nm and a gap width of 0.2 nm for nickel and a wavelength of 283.3 nm and a gap width of 0.7 nm for lead. The analysis results show that manganese at a concentration of 100-5000 μg/mL can interfere with the absorbance of nickel and lead, where the absorbance of nickel and lead increases. Recovery results (Recovery) of nickel, lead and manganese with masking 0.10 M EDTA and extracting nickel, lead and manganese into chloroform with sodium diethyl dithiocarbamate complexing at pH 2 obtained nickel (85.39%), lead (92.63%) and manganese (0.00%). nickel and lead pyrolusite samples before extraction with an average nickel and lead content of 1817.82 ± 9.42 μg/g and 122.81 ± 7.60 μg/g. The nickel and lead content after manganese interference was removed by EDTA 0 masking .1 M at pH 2 and complexed with DDC in chloroform obtained an average content of 1571.32 ± 7.54 μg/g for nickel and 87.65 ± 7.53 μg for lead. Key words: Atomic Absorption Spectrophotometry, Interference, masking EDTA, Extraction, Nickel and Lead.